The Determinants of Government Bond’s Yields for EMU Countries: The Effect of Financial Crisis - Papaconstantinou, Demetrios (2013)
This paper provides an analysis of the determinants of the EMU sovereign spreads with emphasis on the effect of the global financial crisis of 2007/08. We are using econometric techniques that help us to distinguish short-term from the long-term effects of macro-fundamentals and international factors. The financial crisis has as consequence the rapid increase of spreads in some countries and as result it created Euro zone of two speeds. Our results suggest that spreads are determined significantly from both macroeconomic and international factors. Remarkable finding of our research is the outcome of our investigations for the pre-crisis and post-crisis periods. Our results suggest that before the crisis financial markets occurred homogeneity in EMU spreads determinants. Although the increase of heterogeneity in our results showing that after the crisis investors started to reconsider the risk factors of each sovereign issuer. We form the assumption through our results that before the crisis EMU was consider as entity and the risks was equivalent among the members. From our research we can conclude that some sovereign issuers in the EMU were unreasonably priced with low spreads in the before-crisis period. The rapid grow of national debt was one of the consequences, which has as result the appearance of the possibility of economic collapse in some countries due the unsustainable amount of debt. It also raises questions about the viability of a monetary union with political sovereignty and not common fiscal policy.